Syncretization of The Grebeg Suro Ritual Through The Planting of Bull Heads to Strengthen Religious Harmony in The Community of Sumbermujur Village - Wijayanti, Berly; Hidayati, Nur; Shodiq, Muhammad (Proceedings of Annual Conference for Muslim Scholars, 2024)
Grebeg Suro is a centuries-old Javanese tradition celebrated on the first day of Muharram. This ritual-rich tradition holds significant spiritual and symbolic value. One particularly intriguing aspect of Grebeg Suro in Sumbermujur is the practice of planting a cow's head, a fascinating blend of local culture and religious beliefs. This research delves into the syncretic elements within Grebeg Suro rituals and explores the community's interpretation of the tradition. Through qualitative research methods, including observations, in-depth interviews, and documentation, the study reveals that these rituals contribute to the harmony of the religious community in Sumbermujur. The involvement of people from diverse backgrounds demonstrates that religious diversity can positively impact community cohesion. The presence of syncretism fosters mutual appreciation rather than division. The research also examines the philosophical significance of the ritual practices, uncovering the interplay between local traditions and religious teachings. By understanding the syncretic nature of Grebeg Suro, we can appreciate the rich cultural heritage of the Javanese people and their ability to integrate diverse beliefs and practices into a harmonious whole.